HUMOR, LANGUAGE, AND VISUAL INCONGRUITY: A DISCOURSE ANALYSIS OF THE SENGKLEK FAMILY COMIC BY JULIAN SYAHPUTRA - Cahyaningtias, Aisyha; Kurniawan, Muhammad Ardi (ppjbsip, 2026)
This study examines the mechanisms of humor construction in the digital comic Sengklek Family by Julian Syahputra, using a discourse-based analysis of verbal and visual elements. Although previousstudies have explored Indonesian digital comics, humor has rarely been analyzed systematically using amultimodal and pragmatic framework. Drawing on three classical humor theories, superiority, relief,and incongruity, this study identifies how linguistic ambiguity, literalization of idioms, and visualhyperbole generate comedic effects in everyday social contexts. The data consist of 110 episodes fromthe Webtoon platform, analyzed qualitatively using content analysis focusing on humorous panels. Thefindings reveal 112 humor instances: 111 examples of incongruity humor and 1 example of relief humor,with no superiority humor. Incongruity humor is primarily produced through the literal interpretation ofpolysemous expressions that conflict with expected social logic, while relief humor functions asemotional release in tense or taboo situations. From a discourse perspective, humor in Sengklek Familyoperates as a multimodal meaning-making device that constructs social commentary on urban life,linguistic playfulness, and cultural norms. The study contributes to humor scholarship by integrating discourse analysis and multimodal interpretation into digital comic research. Future research should apply critical discourse analysis to examine the ideological dimensions of humor and to explore comparative studies with other Indonesian webcomics.